2018
DOI: 10.1007/s10549-018-5034-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms linking high body mass index to breast cancer etiology in post-menopausal breast tumor and tumor-adjacent tissues

Abstract: Purpose: In postmenopausal women, high body mass index (BMI) is an established breast cancer risk factor and is associated with worse breast cancer prognosis. We assessed the associations between BMI and gene expression of both breast tumor and adjacent tissue in estrogen receptor positive (ER+) and negative (ER-) diseases to help elucidate the mechanisms linking obesity with breast cancer biology in 519 postmenopausal women from the Nurses' Health Study (NHS) and NHSII.Methods: Differential gene expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
1
31
1
Order By: Relevance
“…Fuentes-Mattei et al 21 observed significant upregulation of AKT/mTOR genes in obese vs. normal-weight women with ER+ tumors ( N = 137). However, these findings were not replicated in a study of 519 postmenopausal women 23 . As obesity may affect both gene and protein expression in tumors, we focus on the latter because the mTOR pathway signaling is primarily through post-translational protein phosphorylation 24 , 25 .…”
Section: Discussionmentioning
confidence: 80%
“…Fuentes-Mattei et al 21 observed significant upregulation of AKT/mTOR genes in obese vs. normal-weight women with ER+ tumors ( N = 137). However, these findings were not replicated in a study of 519 postmenopausal women 23 . As obesity may affect both gene and protein expression in tumors, we focus on the latter because the mTOR pathway signaling is primarily through post-translational protein phosphorylation 24 , 25 .…”
Section: Discussionmentioning
confidence: 80%
“…It is of interest that while studies of breast tissue from otherwise healthy OB women [51], OB women with breast cancer [49,50,59], and OB adult mice [60] have consistently demonstrated increased breast inflammation, an association between inflammation and estrogen synthesis and activity has only been observed in some studies. In a study of breast tissue from adult women (average age~36 years) undergoing reduction mammoplasty, Sun et al observed increased cytokine signaling and macrophage infiltration by differential gene expression and pathway analyses; genomic studies were bolstered by IHC studies demonstrating a greater number of CD68+ macrophage inflammatory foci (CLS) in breast tissue from OB than normal weight women.…”
Section: Discussionmentioning
confidence: 99%
“…Mullooly et al [50] also observed increased CLS in benign breast tissue collected from OB breast cancer patients, and CLS were associated with a higher ratio of estrogen to androgen precursors in blood and breast tissue, suggesting increased aromatase activity. Heng et al observed an enrichment of genes related to inflammation and to the early estrogen response pathway in a microarray study of ER+ breast tumor samples from OB compared with normal weight postmenopausal women enrolled in the Nurses' Health Study, but this finding was not replicated in two other large breast cancer cohorts [59]. Lastly, in studies of mammary tissue from OB adult mice [60], pro-inflammatory factor abundance was also strongly correlated with aromatase activity and with expression of two classical ER target genes, PR and TFF1.…”
Section: Discussionmentioning
confidence: 99%
“…Further, RT reduces the long-term risk for local recurrence [5].Beyond RT, systemic treatments such as endocrine therapy are also a mainstay in BC treatment; however, flexible guidelines and patient preferences often leave therapy choice to physicians' discretion although endocrine therapy is recommended for patients whose cancer display any level of estrogen expression [6,7]. Notably, it has been found that endocrine therapy and RT can be safely concurrently administered without danger of weakening disease control [6].Obesity has been implicated as a risk factor in RT resistance, metastasis, and overall poor prognosis in breast cancer [8][9][10]. Furthermore, moderate to severe obesity increases the likelihood of BC recurrence and BC-specific mortality [10,11].…”
mentioning
confidence: 99%
“…Obesity has been implicated as a risk factor in RT resistance, metastasis, and overall poor prognosis in breast cancer [8][9][10]. Furthermore, moderate to severe obesity increases the likelihood of BC recurrence and BC-specific mortality [10,11].…”
mentioning
confidence: 99%